Analysis of Businesses Satisfaction and Loyalty To The Service Quality of Agriculture Tool and Machinery Testing - Dedy Wahyudi; Lilik Noor Yuliati (Pusbindiklat - LIPI, 2015)
System standardization in testing and monitoring agricultural machinery an attempt to anticipate the increasing use of agricultural machinerywho do not meet the technical and economical feasibility standards. At this time there are many agricultural machinery from foreign and domestic untested and not in accordance with the Indonesian National Standard (SNI). Agricultural Machinery Quality Testing Center (BPMA) is one organization that conducts testing agriculture machinery But since the beginning of the current set up has never conducted a survey on customer satisfaction. Yet over time, occurs complaints submitted by businesses agricultural machinery directed to the BPMA. This research examines the relationship between service quality, satisfaction and loyalty businesses that apply for testing equipment and agricultural machinery in the Ministry of Agriculture. Respondents were used in this study are the businesses that produce agricultural machinery as 88 respondents, that all respondents should be the following testing procedures from the beginning until the publication of the report of test results. Based on the results if the data using SEM-based variantis found that the quality of service (tangible, responsiveness, assurance, and empathy) a significant effect on customer satisfaction, and satisfaction significantly influence loyalty.